Hepatitis C virus (HCV) specific immune responses in anti-HCV positive patients without hepatitis C viraemia. Issue 3 (1st March 1999) - Cramp, M E; Carucci, P; Rossol, S; Chokshi, S; Maertens, G; Williams, R; Naoumov, N V
Abstract : BACKGROUND/AIMS: Most patients infected with hepatitis C virus (HCV) develop chronic infection and persistent viraemia. The immune mechanisms responsible for resolution of viraemia remain poorly understood. HCV specific humoral and cellular immune responses in patients with and without viraemia were investigated. METHODS: In vitro T helper (TH ) lymphocyte responses to structural and non-structural HCV proteins were determined by means of proliferative response and cytokine production in 35 anti-HCV positive/HCV RNA negative patients and in 31 patients with chronic HCV infection and persistent viraemia. Humoral responses were determined by measuring HCV specific antibody quantity and specificity. RESULTS: A TH response to two or more HCV proteins was present in 18 of 35 patients with serological viral clearance compared with just one of 31 viraemic patients (p = 0.00001). HCV specific interferon-γ production was increased only in the former group. In contrast, the antibody levels were significantly lower and directed at fewer HCV antigens in patients with undetectable HCV RNA. CONCLUSIONS: Patients without viraemia after HCV infection frequently have strong TH lymphocyte responses of the TH 1 type to multiple HCV antigens many years after the onset of infection, whereas antibody responses are less marked. These results suggest that control of HCV replication may depend on effective TH lymphocyte activation.